Surgical treatment of gastroesophageal reflux disease: total or partial fundoplication? Systematic review and meta-analysis - Rodrigo F Ramos; Suzana Angélica S Lustosa; Carlos Augusto P. de Almeida; Carolina P. da Silva; Delcio Matos (Arquivos de Gastroenterologia, 2011)
CONTEXT: Although the high incidence of gastroesophageal reflux disease (GERD) in the population, there is much controversy in this topic, especially in the surgical treatment. The decision to use of a total or partial fundoplication in the treatment of GERD is still a challenge to many surgeons because the few evidence found in the literature. OBJECTIVE: To bring more clear evidence in the comparison between total and partial fundoplication. DATA SOURCES: A systematic review of the literature and metaanalysis with randomized controlled trials accessed from MEDLINE, LILACS, Cochrane Controlled Trials Database was done. The outcomes remarked were: dysphagia, inability to belch, bloating, recurrence of acid reflux, heartburn and esophagitis. For data analysis the odds ratio was used with corresponding 95% confidence interval. Statistical heterogeneity in the results of the metaanalysis was assessed by calculating a test of heterogeneity. The software Review Manager 5 (Cochrane Collaboration) was utilized for the data gathered and the statistical analysis. Sensitive analysis was applied using only trials that included follow-up over 2 years. RESULTS: Ten trials were included with 1003 patients: 502 to total fundoplication group and 501 to partial fundoplication group. The outcomes dysphagia and inability to belch had statistical significant difference (P = 0.00001) in favor of partial fundoplication. There was not statistical difference in outcomes related with treatment failure. There were no heterogeneity in the outcomes dysphagia and recurrence of the acid reflux. CONCLUSION: The partial fundoplication has lower incidence of obstructive side effects.